Sea water temperature and light intensity at high-Arctic subtidal shallows – 16 years perspective - Bernabé Moreno; Anna Sowa; Kamil Reginia; Piotr Balazy; Maciej Chelchowski; Marta Ronowicz; Piotr Kuklinski (Scientific Data, 2024)
Abstract Manifestations of climate change in the Arctic include an increase in water temperatures and massive loss of sea ice enabling more light penetration. Yet to understand tempo and scale of these parameters change over time, constant monitoring is needed. We present 16-yr long-term datasets of sea water temperature and relative light intensity at two depth strata (8 and 14 ± 1 m) of two hard-bottom sites in southern Isfjorden proper (Spitsbergen, 78°N). The high temporal resolution of the datasets (every 30 min, between 2006–2022) makes them suitable for studying changes at a local scale, correlating environmental variability with observed processes in benthic assemblages, and serving as ground-truth for comparison with, for example, remotely sensed or mooring data. These datasets serve as baseline for long-term investigations in the shallows of a high-Arctic fjord undergoing severe environmental changes.